Factors Affecting Thyroid Volume and the Incidence of Nodules With Goiter School-Aged Children - Sultan Kaba; Murat Doğan; Alpaslan Yavuz; Sinan Kılıç (Çocuk Dergisi)
Objective: This study aimed to analyze the associations between age, sex, anthropometric factors, and thyroid volume as well as to determine the prevalence of goiter and thyroid nodules in school children. Methods: This study included schools governed by the Ministry of Education in Van province. Sonographic evaluations of thyroid glands were conducted in children aged 6–17 years, and measurements of weight, height, waist circumference, hip circumference, and skinfold thickness were obtained from the participants. Results: A total of 2284 school children were included in the study. The median age of the participants was 11.08 years. It was observed that thyroid volume exhibited a positive correlation with age, body surface area, body mass index, height, weight, waist circumference, hip circumference, triceps skinfold thickness, and subscapular skinfold thickness (p < 0.008). When assessing the association between age and goiter prevalence based on World Health Organization parameters, 10.2% of children and adolescents developed goiter, and 0.8% of these cases also had a nodule. Among girls, the rates were 9.4% and 1% for goiter and nodules, respectively, whereas among boys, the rates were 11.3% and 0.7%, respectively. Conclusions: Thyroid volume was affected by age, weight, subcutaneous tissue thickness, waist circumference, and BSA. Goiter remains a serious public health problem among school-age children in Van province.